Role of BDNF/ProBDNF Imbalance in Postoperative Cognitive Dysfunction by Modulating Synaptic Plasticity in Aged Mice - Xue, Ziyi; Shui, Min; Lin, Xiaowan; Sun, Yi; Liu, Jianhui; Wei, Changwei; Wu, Anshi; Li, Tianzuo (Frontiers in Aging Neuroscience, 2022)
Postoperative cognitive dysfunction (POCD) is a disturbing neurological complication in patients undergoing anesthesia and surgical procedures. Brain-derived neurotrophic factor (BDNF) and its precursor proBDNF binding to their corresponding receptors tyrosine kinase (TrkB) and p75 neurotrophin receptor (p75NTR) exert a quite opposite biological function in the neuron survival and the synaptic function. This study aimed to demonstrate the critical role of the BDNF/proBDNF ratio in modulating synaptic plasticity, which further leads to the anesthesia/surgery induced POCD. It also showed that the exogenous BDNF or p75NTR inhibitor could ameliorate cognitive dysfunction. In detail, 16-month-old C57BL/6 mice were subjected to a stabilized tibial fracture surgery with isoflurane anesthesia to establish the POCD animal model. The mice were then micro injected with either p75NTR inhibitor or exogenous BDNF into dorsal hippocampus. Behavioral experiments were performed by open field and fear conditioning tests. Western blotting was also used to measure the expression levels of BDNF, proBDNF, TrkB, p-TrkB, p75NTR and synapse proteins. Golgi staining and electrophysiology were applied to evaluate the neuronal synaptic plasticity. Here we demonstrated the anesthesia/surgery induced a reduction of BDNF/proBDNF, which negatively regulating the synaptic function in hippocampus and subsequently leading to the cognitive impairment in aged mice. P75NTR inhibitor and exogenous BDNF could attenuate cognitive deficits by rescuing the dendritic spine loss and long-term potentiation (LTP) via altering the BDNF/proBDNF ratio. This study unveiled the BDNF /proBDNF ratio in the hippocampus played a key role in anesthesia/surgery induced POCD. Thereby, tuning the ratio of BDNF/proBDNF is supposed to be a promising therapeutic target for POCD.